Flavonoids as Natural Inhibitors of Jack Bean Urease Enzyme - A. J. Awllia, Jalaluddin; AL-Ghamdi, Maryam; Huwait, Etimad; Javaid, Sumaira; Atia-tul-Wahab; Rasheed, Saima; Iqbal Choudhary, M. (Letters in Drug Design & Discovery, 2016)
Enzyme urease plays an important role in several pathologies, such as urolithiasis, urinary catheter encrustation, hepatic encephalopathy, peptic ulcers, and gastric cancers. Its inhibition, therefore, has a major therapeutic significance. For this purpose, nine natural flavonoids 1-9 were evaluated for their urease inhibitory activity. Five of them (i.e. 1, 3, 7, 8, and 9) showed a urease inhibitory activity with IC50 values between 14.2 – 132.9 μM. Compounds 3, 8, and 9 showed a potent activity (IC50 =19.4 ± 1.39, 14.2 ± 0.30 and 17.7 ± 0.23 μM, respectively), in comparison to the standard urease inhibitor, acetohydroxamic acid (IC50 = 41.5 ± 1.50 μM). Furthermore, compounds 1, 7, and 9 exhibited a competitive mode of inhibition. Compounds 1, 3, 7, 8 and 9 were finally tested for cytotoxicity by using mouse fibroblast cell line (3T3 cell line) assay. Compounds 1, 3 and 7 were found non-cytotoxic, while compounds 8 and 9 showed some level of toxicity (IC50 = 18.75 ± 0.45 and 13.01 ± 0.70 μM, respectively). Present study identifies flavonoid 8 as a lead for further investigation towards designing novel urease inhibitors for the treatment of diseases associated with ureolytic bacteria.
Keywords: Flavonoids